2005
DOI: 10.1242/jcs.02718
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of a double agent: CDK7 in cell-cycle control and transcription

Abstract: In metazoans, cyclin-dependent kinase 7 (CDK7) has essential roles in both the cell-division cycle and transcription, as a CDK-activating kinase (CAK) and as a component of the general transcription factor TFIIH, respectively. Controversy over its double duty has been resolved, but questions remain. First, how does CDK7 achieve the dual substrate specificity necessary to perform both roles? Second, is there a deeper connection implied by the dichotomy of CDK7 function, for example similar mechanisms controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
289
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(298 citation statements)
references
References 116 publications
4
289
2
3
Order By: Relevance
“…Inhibition of CAK phosphorylation of the retinoblastoma tumorsuppressor protein leads cells to exit the cell-cycle G 1 phase (Wu et al, 2001). On the other hand, TFIIH-containing CAK mediates transcription initiation by phosphorylating the largest subunit of RNA polymerase II (Nigg, 1996;Fisher, 2005). These studies suggest that changes in CAK phosphorylation of different substrates modulate cell-cycle G 1 exit and transcriptional control.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Inhibition of CAK phosphorylation of the retinoblastoma tumorsuppressor protein leads cells to exit the cell-cycle G 1 phase (Wu et al, 2001). On the other hand, TFIIH-containing CAK mediates transcription initiation by phosphorylating the largest subunit of RNA polymerase II (Nigg, 1996;Fisher, 2005). These studies suggest that changes in CAK phosphorylation of different substrates modulate cell-cycle G 1 exit and transcriptional control.…”
Section: Introductionmentioning
confidence: 95%
“…The S77 of RARa (RARaS77) is the main residue phosphorylated by CAK . CAK exists in cells as free CAK or as part of the general transcription factor IIH (TFIIH) complex (Nigg, 1996;Fisher, 2005). Free CAK regulates cell-cycle G 1 progression by phosphorylation activation of CDKs (Nigg, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified two non-overlapping sets of Cdks in metazoans: Cdk1, Cdk2, Cdk4 and Cdk6, dedicated to cell-division control, and Cdk8 and Cdk9, primarily implicated in transcription [26]. However, the Cdk7 complex cannot be easily classified [26] as Cdk7/Cyclin H has a dual role: first, as the CAK of cell cycle Cdks, and second, as a component of the general transcription factor TFIIH, phosphorylating the CTD of RNA polymerase II.…”
Section: Discusssionmentioning
confidence: 99%
“…However, the Cdk7 complex cannot be easily classified [26] as Cdk7/Cyclin H has a dual role: first, as the CAK of cell cycle Cdks, and second, as a component of the general transcription factor TFIIH, phosphorylating the CTD of RNA polymerase II.…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation